Contributing to reading comprehension through Science and Technology education - Keulen, Hanno van; Boendermaker, Conny (Design and Technology Education: An International Journal, 2020)
In this study, an educational development approach is investigated aiming at improving reading comprehension outcomes in primary education through inquiry and design-based Science & Technology teaching. The context is societal pressure to increase the likelihood that more students, later in their life, will aspire for careers in technology-intensive professions. However, schools are under more pressure to focus on core subjects, such as language. Integrated Science & Technology and Language education may overcome this problem. In this study, students from Years/Grades 3-6 (9- to 12-year-olds) received an experimental treatment, in which regular reading comprehension lessons were replaced by inquiry and design-based projects with a strong focus on oral language. Before and after, their performance on tests for reading comprehension was measured. No significant differences were found from performance in a control group, who received the regular reading comprehension lessons, but hardly any Science & Technology lessons. In the experimental group, teachers used the Skills Rubric Inquiry and Design and reported that students’ skills for inquiry and design improved considerably. Substantial professional support in the form of weekly meetings in a professional learning community was necessary to achieve these goals. Initially, the teachers involved had little knowledge of Science & Technology and low self-efficacy with regard to teaching this subject, but teacher attitude towards teaching Science & Technology improved considerably during the project. It was concluded that integrating Science & Technology and language education is a complicated yet rewarding approach.